2021
DOI: 10.1097/jcma.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder syndrome is associated with detrusor overactivity and abnormal voiding pattern in nulliparous women

Abstract: Background: Pregnancy and childbirth are frequently associated with overactive bladder syndrome (OAB). However, the role of parous effects in OAB among nulliparous (NP) women remains controversial. Methods: This study investigated abnormal voiding patterns and detrusor overactivity (DO) among NP women with OAB in comparison with parous women. From August 2011 to December 2018, 906 patients met the inclusion criteria for participation and were divided in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The current study might be equated to other studies conducted with similar sampling techniques in cross sectional female populations. (5,7,11) Hansen et al reported that loss of urine during sexual intercourse was 3 times more prevalent in primiparous women compared with their age-matched nulliparous counterparts. (23)…”
Section: Discussionmentioning
confidence: 99%
“…The current study might be equated to other studies conducted with similar sampling techniques in cross sectional female populations. (5,7,11) Hansen et al reported that loss of urine during sexual intercourse was 3 times more prevalent in primiparous women compared with their age-matched nulliparous counterparts. (23)…”
Section: Discussionmentioning
confidence: 99%
“…9 The NP had statistically higher rates of DO and female voiding dysfunction, including decreased peak flow and decreased mean flow, compared with NSD or C/S did. 9 As expected, the NP were younger, and had higher maximum urethral closure pressure (MUCP) and longer functional urethral length (FUL) than NSD or C/S did. 9 The current article is interesting and worthy of discussion.…”
mentioning
confidence: 82%
“…8 We are happy to introduce the current article from the Taipei Medical University Hospital to focus on the topic addressing OAB in NP women. 9 The authors retrospectively enrolled 906 women with OAB, which were further separated into three groups as 221 NP, 571 parous women via normal spontaneous vaginal delivery (NSD), and 114 parous women via cesarean section delivery (C/S) to compare the urodynamic changes among three groups via urodynamic study (UDS). 9 The NP had statistically higher rates of DO and female voiding dysfunction, including decreased peak flow and decreased mean flow, compared with NSD or C/S did.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Female pelvic floor disorders, a chronic, complex and inflammatory disease, including overactive bladder, stress urinary incontinence, pelvic organ prolapse, and interstitial cystitis (IC), are increasing prevalent on a global scale, which significantly affect quality of life, such as increased health care visits, disturbance of sleep, higher rates of depression and anxiety, increased risk of fall-related injuries, increased risk of urinary tract infection, and reduced work productivity, leading to significant social and economic burdens. [1][2][3][4][5][6][7] Among these female pelvic floor disorders, IC (also called as bladder pain syndrome) may be one of the most troublesome disorder, because etiology is still uncertain, and diagnosis remains by exclusion as well as the diagnosis is often delayed in the patient's journey, contributing to a profound impact on the emotional, psychological, and social well-being of the patient. [5][6][7][8] Due to aforementioned reasons, the management of women with IC is still a biggest challenge for both physicians and patients.…”
mentioning
confidence: 99%